(untitled) (Eurasian Research Bulletin, 2023)
The influence of defects induced by fast neutron irradiation on the carrier removal rate in reference p-Si and neutron transmutation doped silicon (p-Si < B, P >) was investigated by the Hall effect and specific resistance techniques at room temperature. It is shown that the carrier removal rate is larger in p-Si < B, P >, than that of p-Si . The barrier model was proposed for explanation of the observed effect..